Effective Digital Marketing Strategies to Increase Sales and Reach of MSMEs in Banjarbaru City - Effendy, Ibrahim Rully; Widyanto, Rinto; Maulana, Andika Jaya; Wahyudi, Wahyudi (Pasundan Social Science Development, 2025)
Increasing sales and market reach is a major challenge for Micro, Small, and Medium Enterprises (MSMEs) in Banjarbaru City. In the digital era, implementing an effective digital marketing strategy can be a solution to expand the market and increase sales volume. This study aims to identify and analyze digital marketing strategies that can be implemented by MSMEs in Banjarbaru City to achieve these goals. Using a qualitative approach, this study collected data through interviews and case studies on several MSME actors who have utilized digital marketing. The results of the study show that the use of social media, search engine optimization (SEO), and paid advertising (Google Ads, Facebook Ads) are the most effective strategies in increasing the visibility and competitiveness of MSMEs. In addition, managing interesting content and good interaction with consumers have also been shown to play an important role in building customer loyalty. Overall, digital marketing strategies can have a positive impact on increasing sales and reach of MSMEs in Banjarbaru City, but proper and consistent implementation is needed so that optimal results can be achieved.